Ocorrência de lesões de pele e mucosa associadas a dispositivos médicos em recém-nascidos - FARIA, Maíla Fidalgo de (2018)
The fragile skin of newborns makes this population more propitious to the development of lesions. Hospitalization during the neonatal period increases the risk of skin lesions due to procedures performed, impaired mobility and the use of various medical devices, making it necessary to establish protocols for prevention and treatment of skin lesions. This research aimed to identify the occurrence of skin and mucosal lesions and associated factors related to the use of medical devices in hospitalized newborns. This is a longitudinal, quantitative and observational study that occurred in a pediatric and Neonatal Intensive Care Unit (NICU) of a large public teaching hospital in the State of Minas Gerais, Brazil. The study included all newborns admitted by the NICU, regardless of the gestational age of the mother, and that used at least one of the medical devices analyzed in the study. Those who had lesions caused by medical devices prior to NICU admission were excluded. The study included 85 newborns (n = 85), admitted by NICU during the months of February to August 2018. The body surface was observed once a day until 28 days of life or in case of discharge from hospital, death or hospital transfer. Data were collected using the Neonatal Skin Condition Scale and an instrument that included variables on medical devices in use - materials used for skin protection – and sociodemographic and clinical variables. The data were entered, validated and stored in Microsoft Office Excel® and analyzed using the Statistical Package for the Social Sciences®. The research was initiated after approval of the Ethics Committee in Research, opinion nº 2.288.994, and assent of the legal guardian of the child. Of the 85 (n) newborns evaluated, 52 (61.2%) were males; 66 (77.6%) were born by cesarean section; 64 (75,3%) presented premature chorioamniorrexis for less than 24 hours; 65 (76,4%) were preterm newborns; 29 (34.1%) had low birth weight. The average Apgar in the first minute of life was 6.84 and in the 5th minute it was 8.33. Regarding admission, 44 participants (51.8%) came from the surgical ward and 76 (89.4%) had 0 to 2 days of life. At the beginning of the data collection, 77 (90.6%) had up to 7 days of life. The mean number of monitoring days for the evaluation of newborns was 14.94 days, being the minimum of 1 day and the maximum of 28 days. The mean number of devices used during the data collectionperiod was 4.67, and the orogastric tube was used for 85 (100%) of the newborns. About the materials used by the NICU as protective measures for the skin and mucosa, 76 newborns (89.4%) used some type of material to protect the skin, being microporous adhesive tape the most used, identified in 70 (82.4%) of the participants. The newborns presented similar skin conditions on the first and last day of the neonatal period, with averages of 4.00 and 4.19 points, respectively, according to the Neonatal Skin Condition Scale, which ranks 3 points to the better skin condition and 9 points to the worse. 62 of the newborns (72.9%) presented skin or mucosal lesions caused by the use of some of the medical devices studied; 32 (37.6%) had 1 to 3 lesions, being the bruises the most observed lesions, identified in 55 (64.7%) of the participants. The bivariate analysis showed that there was a weak correlation (r = 0.28) between the mean score of the skin condition of the newborn and the number of lesions and there was a moderate correlation (r = 0.50) between the number of medical devices used and the number of lesions. Multiple linear regression analysis showed that there was a statistically significant relationship between the total number of devices used (p = 0.001) and age (p = 0.033) with the number of skin and mucosal lesions in the period evaluated. In conclusion, most of the participants presented skin lesions associated with medical devices and the number of medical devices used and the age of the newborn were predictors for this occurrence. It is expected that these findings may support the implementation of measures for the prevention of injuries in newborns associated with medical devices, contributing to a safe and quality care for this population.